Exploring the history of neuropsychology : selected papers - Benton, Arthur Lester, 1909-2006 (Oxford University Press, 2000)
Arthur Benton has long been recognized as a distinguished researcher, an influential educator, and a gifted writer. Early in his career, he was struck by the extreme divergence in the acceptance and usage of concepts and terms such as 'agnosia', 'amnesic aphasia', and 'apraxia' by leading figures in the then young field of neuropsychology/behavioral neurology. This prompted him to explore the literature of 19th century neurology and led to an abiding interest in the historical background of current developments, which often proved to be the outgrowth of earlier formulations. In this collection o.